Evaluation of the surgical treatment of humeral shaft fractures and comparison between surgical fixation methods - Gonçalves,Felipe Fernandes (2018)
ABSTRACT Objective: The objective of this study is to analyze the surgical results of humeral shaft fracture treatment and describe its epidemiology. Methods: Retrospective study that identified all patients treated with surgical fixation of humeral shaft fractures between December of 2014 and June of 2016 in a trauma reference center. All medical records were reviewed in search of epidemiological data referent to the trauma and post-operative results, including radiographic healing of the fracture and related complications. Results: Fifty-one patients were included, mostly male (78.4%), with an average age of 35.02 years. The most common trauma mechanism was a traffic accident (56.9%) followed by same-level falls (17.6%). No statistically significant difference was found between healing time comparing surgical fixation techniques, including open reduction and internal fixation, minimally invasive technique, intramedullary nailing, and external fixation. Conclusion: Although each technique has inherent advantages and disadvantages, all fixation methods proved to be adequate options for the surgical treatment of humeral shaft fractures with high rates of healing and low rates of post-operative complications.